Metasploit Penetration Testing Cookbook : Evade antiviruses, bypass firewalls, and exploit complex environments with the most widely used penetration testing framework, 3rd Edition. - Jaswal, Nipun (Packt Publishing, 2018)
Metasploit is the world's leading penetration testing tool and helps security and IT professionals find, exploit, and validate vulnerabilities. Metasploit allows penetration testing automation, password auditing, web application scanning, social engineering, post exploitation, evidence collection, and reporting. Metasploit's integration with ...